Study of outcome of major depressive disorder treatment as per evidence based treatment protocol devised by department of psychiatry - R S Rawat; L R Kataria; K J Tanna (Journal of Integrated Health Sciences)
Background: Major depressive disorder (MDD) is characterized by depressed mood along with excessive fatigability, psychomotor agitation or retardation, weight loss or gain, patients diagnosed with MDD decreased interest in pleasurable activities and feelings of hopelessness and worthlessness for a minimum period of 2 weeks. Guidelines like NICE guidelines, Indian Psychiatric Association guidelines that are available might not be specific for all patients. Therefore, department of Psychiatry SBKSMI&RC designed Evidence Based Treatment Protocols for the same. Hence, patients attending psychiatry OPD are treated with this protocol. Our aim was study of outcome of Major Depressive Disorder treatment as per evidence based treatment protocol devised by Department of Psychiatry. Methodology: Treatment naïve 50 MDD subjects were recruited. The severity was assessed using Montgomery-Asberg Depression Rating Scale (MADRS). All subjects were given antidepressant monotherapy from the following group-Selective Serotonin Reuptake Inhibitors (SSRI), Selective Norepinephrine Reuptake Inhibitors (SNRI), Norepinephrine Dopamine Reuptake Inhibitors (NDRI) & Noradrenergic & specific Serotonergic Antagonist (NaSSA) at optimal dosage for 8 weeks after which MADRS was repeated. Subjects still symptomatic (score>6) were augmented with another antidepressant at optimal doses from group other than what was given at baseline for next 8 weeks after which the outcome was assessed. Results: 72% of patients became asymptomatic (MADRS score <6) after 8 weeks of treatment. Majority of improvement was seen in mild category. 80% became asymptomatic after 8 weeks of augmentation & this was most effective in severe category. Conclusion: 80% of subjects became asymptomatic who received adequate drug trial at optimal doses according to stage-1 of our treatment protocol for MDD which implies that evidence based protocol that we designed for MDD is efficacious.